Isolation of a novel quercetin derivative from Terminalia chebula and RT-PCR-assisted probing to investigate its DNA repair in hepatoma cells - Kallyadan Soumya; Karickal Raman Haridas; Jesna James; Sudhakaran Sudheesh (Wolters Kluwer Medknow Publications, 2024)
Background and purpose: DNA damage can lead to carcinogenesis if replication proceeds without proper repair. This study focused on the purification of a novel quercetin derivative present in Terminalia chebula fruit and studied its protective role in hepatoma cells due to H2O2-DNA damage. Experimental approach: The pure compound obtained from the silica gel column was subjected to structural characterization using spectroscopic techniques. MTT assay was employed to select a non-toxic concentration of the isolated compounds on HepG2 and Chang liver cells. The antigenotoxic property of the compound on HepG2 and Chang liver cells was carried out by alkaline comet assay. Analyses of expression levels of mRNA for two DNA repair enzymes, OGG1 and NEIL1, in HepG2 and Chang liver cells, were carried out using the RT-PCR method. Findings/Results: The pure compound obtained from the fraction-5 of diethyl ether extract was identified as a novel quercetin derivative and named 7-(but-2-en-1-yloxy)-2-(4(but-2-en-1-yloxy)-3-hydroxyphenyl)-3- (hexa-2,4-dien-1-yloxy)-6-hydroxy-4H-chromen-4-one. This compound recorded modest toxicity at the highest concentration tested (percentage cell viability at 100 μg/mL was 64.71 ± 0.38 for HepG2 and 45.32 ± 0.07 for Chang liver cells). The compound has demonstrated noteworthy protection against H2O2-induced DNA damage in both cell lines. Analyses of mRNA expression levels for enzymes OGGI and NEIL1 enzymes in HepG2 and Chang liver cells asserted the protective role of the isolated compound against H2O2-induced DNA damage. Conclusion and implication: The protective effect of a novel quercetin derivative isolated from T. chebula in the hepatoma cells is reported here for the first time.